Influence of Internet Information Sources and Utilization on Library and Information Science Diploma Students on Academic Achievement in Kaduna State - Boor, C. H. M; Salisu, M. S; Dauda, M.; Auwal, S. (Kashere Journal of Education, 2021)
This study investigated the influence of Internet information sources and utilization on Library and Information Science (LIS) diploma students for academic achievement in Kaduna State. Four research questions were raised. Survey research design was adopted. The population of the study consists of all tertiary institutions offering diploma in LIS programme in Kaduna State with eight hundred and seventy-two (872) diploma students and lecturers. Questionnaires were the instrument administered on a sample size of eight hundred and seventy-two (872) diploma two students and their lecturers while only seven hundred and five (705) copies were returned using a purposive sampling technique. Data collected were analyzed using simple percentages and frequency table. Results of the finding explain the frequency of information sources and access to internet information for their academics’ goals as indicated in table ii, with 416(99.0%) of the respondents while 16 (2.3%) Connect the internet to making friendship was the last by diploma students and their lecturers. Recommendations were made, as more ideas should be put in place to provide the LIS, diploma students and their lecturers with internet services since it gives quick access to the needed educational formation without any impediment.